Implementasi Sensor LDR dalam Pengembangan Lampu Otomatis untuk Efisiensi Energi di Desa Sumbersawit - Moch Yusuf Asyhari; Inung Diah Kurniawati; Bryan Ricky Christoffel; Ilman Winas Saputra (Jurnal Pelayanan Masyarakat, 2025)
Street lighting is very important as a road facility at night, especially in rural areas. Sumbersawit Village, Sidorejo District, Magetan Regency has a problem of lack of adequate lighting system around village roads and public areas. Therefore, a breakthrough is needed to overcome this problem. One way is to hold community service in Sumbersawit Village through LDR sensor implementation activities in developing automatic lights for energy efficiency. This activity is carried out through five main stages, which include: (1) survey and identification of needs, (2) system design and manufacture, (3) socialization and education, (4) installation of automatic lighting system, and (5) evaluation and follow-up. This community service activity was welcomed by the village apparatus and the Sumbersawit village community, so that the activity can run smoothly.